If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2X + 1 = -1x + 2 Reorder the terms: 1 + 2X = -1x + 2 Reorder the terms: 1 + 2X = 2 + -1x Solving 1 + 2X = 2 + -1x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2X = 2 + -1 + -1x Combine like terms: 1 + -1 = 0 0 + 2X = 2 + -1 + -1x 2X = 2 + -1 + -1x Combine like terms: 2 + -1 = 1 2X = 1 + -1x Divide each side by '2'. X = 0.5 + -0.5x Simplifying X = 0.5 + -0.5x
| -x+(-x)+(-x)+(-z)= | | 1.6k=5.75 | | 2x+12=3x-9 | | (x^2)+30x-2000=0 | | n-11=66 | | 11y+5=3(-5+2y) | | -.9x^2+45x=0 | | 8x-12-6x-1=1 | | v-52=29 | | 2(6x-10)=31-3(5-3x) | | -24x+-6+7x+9x-27=4 | | p-6=43 | | h*7=15 | | -3x^2+36x-33=0 | | a^2-10+9a=0 | | 9(2x-3)=27 | | 6x+29=-4x-1 | | 7x=9+-3(x+1) | | 3y+y=-40 | | -3(1-n)=6-6n | | 10(v+2)-4v=3(2v+1)-12 | | 17-5(-7-8)+1= | | b-34=11 | | 6x+29=-4x | | 500+35g=55h | | w+-30=-52 | | 34=y-18 | | 7y=-98 | | b+13=42 | | -56=74+10x | | -3(2x-2)=24 | | 8t-10-2t=-6+10+9t |